Analysis of Land Rights Certificate Overlapping Occurrence - Suryajaya, Jonathan Chandra; Handayani, I Gusti Ayu Ketut Rachmi; Karjoko, Lego (Siber International Journal of Advanced Law (SIJAL), 2025)
Article 4 of the UUPA states that based on the right of control by the state, various types of land rights are determined that can be granted to individuals or groups. The purpose of this study is to determine To analyze and review the Legal Basis for the issuance of land title certificate. To analyze and review the Responsibility of the Land Office for the certificate that was canceled in the State Court Decision. The results of this study are that the cancellation of land title certificate can cause legal uncertainty for the community and require the government to increase supervision and improvements in the land system in order to prevent similar cases in the future. In addition, the responsibility of the Land Office in this case is in the spotlight, where there should be an increase in accuracy in data collection and better coordination between agencies so that there is no issuance of duplicate certificates.